2021
DOI: 10.26452/ijrps.v12i4.4875
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Post Partum Depression Among Postnatal Women At A Tertiary Care Centre Using Edinburgh Post Partum Depression Scale

Abstract: Postpartum depression is a grave mental health problem, which is more prevalent than society realizes and poses great risk. It has been associated with lack of breastfeeding, aversion towards the baby and negative impact on the development of the child. A total of 300 women who delivered between January 14 to March 31 of 2020 at Saveetha Medical College and Hospital were chosen following ethical clearance. After explaining the aspects of the Edinburgh Postpartum Depression Scale in their native language, the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…[ 1 ] In South India, the burden of PPD in rural south Karnataka was 11% in 2022, [ 10 ] 31.3% in 2021, [ 11 ] and 21.5% in 2019. [ 12 ] The prevalence of PPD in Chennai in 2021 was 14%, [ 13 ] and in 2019, 9.5% of primary mothers in Kerala had PPD [ Table 1 ]. [ 14 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] In South India, the burden of PPD in rural south Karnataka was 11% in 2022, [ 10 ] 31.3% in 2021, [ 11 ] and 21.5% in 2019. [ 12 ] The prevalence of PPD in Chennai in 2021 was 14%, [ 13 ] and in 2019, 9.5% of primary mothers in Kerala had PPD [ Table 1 ]. [ 14 ]…”
Section: Resultsmentioning
confidence: 99%
“…Another study, which was conducted in Jeddah city in Saudi Arabia in 2021, found that a history of previous depression, experience with difficult life events, and specific attitudes toward pregnancy were all significantly associated with PPD [ 12 ]. Additionally, a study from the Obstetrics ward in Saveetha Medical College and Hospital in India concluded that a lack of social support, low socio-economic status, and family disharmony were significantly associated with PPD [ 17 ]. A study conducted in Pakistan in 2021 found several risk factors for PPD, including a previous history of depression, an infant with anomalies, an unplanned pregnancy, gestational diabetes, and any comorbidity in the mother [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that women who underwent spontaneous vaginal delivery were at a higher risk of developing PPD. The previously mentioned study from the Obstetrics ward in Saveetha Medical College and Hospital in India found that women who had a vaginal delivery rather than a CS had a higher prevalence of PPD [ 17 ]. A study conducted in Al-Madinah city in Saudi Arabia in 2021 found that women who delivered spontaneously through a vaginal route had an almost three times greater risk of developing PPD than those who delivered via CS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations